France : Financial Sector Assessment Program-Detailed Assessment of Observance of CPSS/IOSCO Recommendations for Securities Settlement Systems and for Central Counterparties. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses key findings of the Detailed Assessment of LCH.Clearnet SA Observance of the Committee on Payment and Settlement Systems/International Organization of Securities Commission (CPSS-IOSCO) Recommendations for Central Counterparties. The findings reveal that LCH.Clearnet SA displays a high level of observance of the CPSS/IOSCO recommendations. It has a sound, coherent, and transparent legal basis. It has developed an adequate risk-management framework to address financial and operational risks. LCH.Clearnet SA governance arrangements and composition of Boards and management are well defined and adequately staffed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet